VALUASI EKUITAS PERUSAHAAN UNTUK MENDAPATKAN KEWAJARAN HARGA SAHAM DALAM PROSES IPO (STUDI KASUS PADA PERUM PEGADAIAN) - , Nanik Rahmawati ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Perum Pegadaian is one of the BUMN that are planned will be doing an IPO in the near future. The purpose of this IPO is to seek alternative financing through capital markets to develop business. During the time funding source Perum Pegadaian derived from debt with debt ratio reaches 84%. The purpose of this study was to assess the equity of the company as a basis to obtain a fair share price for the IPO. The study begins by analyzing the business environment and financial performance first, to determine how the companyâs business prospects in the future. Based on the results of the analysis, then the research continued with equity valuation by using the Discounted Cash Flow method (DCF) with the model of Free Cash Flow to Equity (FCFE) and Relative Valuation method with PER and PBV as multiple factor. To obtain the present value of FCFE is using cost of equity as a discount factor that estimated with the Capital Asset Pricing Model (CAPM). The Risk Free Rate is calculated by using the average interest rate of SBI period of one month at a certain period. In this experiment, two beta estimated based on two different assumptions. The first assumption is Perum Pegadaian have a high financial leverage, so it should be using levered beta. The second is using beta of industry average with assumption Perum Pegadaian be able to manage risks on its debt properly and for the reason, On the Relative Valuation approach, PER and PBV that used for valuating is owned by two companies that equivalent with Perum Pegadaian This research has resulted in equity value of Perum Pegadaian is Rp.25.9 Trillion by using DCF method with levered beta, and Rp.37, 7 Trillion with average industry beta. The calculation result is greater than the calculation of Relative Valuation method by multiple factor PER and PBV respectively amounted to Rp.13, 05 Trillion and Rp.9, 08 Trillion.